Deoxyelephantopin ameliorates lipopolysaccharides (LPS)-induced memory impairments in rats: Evidence for its anti-neuroinflammatory properties - Andy, Shathiswaran N.; Pandy, Vijayapandi; Alias, Zazali; Kadir, Habsah Abdul (Elsevier, 2018)
Aim: Neuroinflammation is a critical pathogenic mechanism of most neurodegenerative disorders especially, Alzheimer's disease (AD). Lipopolysaccharides (LPS) are known to induce neuroinflammation which is evident from significant upsurge of pro-inflammatory mediators in in vitro BV-2 microglial cells and in vivo animal models. In present study, we investigated anti-neuroinflammatory properties of deoxyelephantopin (DET) isolated from Elephantopus scaber in LPS-induced neuroinflammatory rat model. Materials and methods: In this study, DET (0.625. 1.25 and 2.5 mg/kg, i.p.) was administered in rats for 21 days and those animals were challenged with single injection of LPS (250 μg/kg, i.p.) for 7 days. Cognitive and behavioral assessment was carried out for 7 days followed by molecular assessment on brain hippocampus. Statistical significance was analyzed with one-way analysis of variance followed by Dunnett's test to compare the treatment groups with the control group. Key findings: DET ameliorated LPS-induced neuroinflammation by suppressing major pro-inflammatory mediators such as iNOS and COX-2. Furthermore, DET enhanced the anti-inflammatory cytokines and concomitantly suppressed the pro-inflammatory cytokines and chemokine production. DET treatment also reversed LPS-induced behavioral and memory deficits and attenuated LPS-induced elevation of the expression of AD markers. DET improved synaptic-functionality via enhancing the activity of pre- and post-synaptic markers, like PSD-95 and SYP. DET also prevented LPS-induced apoptotic neurodegeneration via inhibition of PARP-1, caspase-3 and cleaved caspase-3. Significance: Overall, our studies suggest DET can prevent neuroinflammation-associated memory impairment and neurodegeneration and it could be developed as a therapeutic agent for the treatment of neuroinflammation-mediated and neurodegenerative disorders, such as AD.